2014
DOI: 10.4034/rbcs.2014.18.04.03
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da Capacidade Funcional e da Limitação Física em Sujeitos Pós-Revascularização Miocárdica

Abstract: 1 2 3 RESUMO Objetivo: Avaliar a capacidade funcional e a limitação física, em pacientes submetidos à cirurgia de revascularização do miocárdio (CRVM) com seis meses do pós-operatório. Material e Métodos: Foram estudados 28 pacientes com doença arterial coronariana, submetidos à CRVM entre novembro de 2008 e abril de 2009. Foram avaliadas a capacidade funcional e a limitação por aspectos físicos pela apuração dos respectivos domínios presentes no questionário padronizado Medical Outcomes Study -short form 36 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…According to Lisboa et al [ 22 ] , heart surgery exerts a positive impact on the quality of life of patients in all domains, especially three months after the procedure. Moraes et al [ 23 ] found an increase in general quality of life and the physical domain six months after myocardial revascularization surgery, which translates to an increase in the capacity to perform activities that were not possible in the preoperative period. The improvement in these domains was greater in individuals who practiced physical activity regularly after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lisboa et al [ 22 ] , heart surgery exerts a positive impact on the quality of life of patients in all domains, especially three months after the procedure. Moraes et al [ 23 ] found an increase in general quality of life and the physical domain six months after myocardial revascularization surgery, which translates to an increase in the capacity to perform activities that were not possible in the preoperative period. The improvement in these domains was greater in individuals who practiced physical activity regularly after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…These differences are mainly due to the different moments in which the studies were conducted, the therapeutic resources available and also the different tools used to evaluate patients' quality of life. Whereas there has been improvement of multiple components, such as functional capacity and physical limitation, vitality, emotional aspects, social aspects and general health status (5)(6)(7)(8) , there is also the interference of some essential aspects in the maintenance of quality of life, such as the presence of intense postoperative pain (9) , postoperative pulmonary complications (pleural effusion, atelectasis, pneumothorax, pulmonary embolism, acute pulmonary respiratory failure and bronchopneumonia) (10) , cognitive deficit (11) , and psychological changes, such as anxiety and depression (12) .…”
Section: Introductionmentioning
confidence: 99%